PP.23.16: BRAIN NATRIURETIC PEPTIDE IN HYPERTENSIVE PATIENTS ON REGULAR HEMODIALYSIS. (June 2015) - Charfeddine, S.; Abid, L.; Mnif, K.; Jarraya, F.; Abid, D.; Kammoun, S.
Abstract : Objective: Brain natriuretic peptide (BNP) quantification is a useful cardiovascular diagnostic and prognostic test. In renal failure its use may have constraints, as it depends on renal clearance and concomitant volume overload. The aim of this study was to evaluate the clinical usefulness of BNP in hypertensive patients on maintenance hemodialysis (HD). Design and method: We measured BNP levels in 30 patients immediately before and after HD. All patients had preserved left ventricular ejection fraction (LVEF > 50%) and underwent 48-hours ambulatory blood pressure measurement. Cardiac parameters were evaluated by echocardiography. Results: The left ventricular mass index (LVMi) and BNP levels decreased significantly after HD (p < 0.001). LVMi was significantly associated with the duration of hypertension (p = 0.03). After HD, LVMi was significantly associated to the diurnal, nocturnal and 48-hours ambulatory blood pressure. BNP levels were associated to diastolic blood pressure and LVMi before and after HD. A BNP cut-off value of 68.91 pg/mL after HD resulted in 81.8% specificity and 100% sensitivity for the presence of left ventricular hypertrophy (LVH), (AUC ROC: 0.864) in hypertensive patients. Conclusions: BNP had strong associations with prevalent LVH in hypertensive patients on hemodialysis.